EKSTRAKSI 1,8-CINEOLE DARI MINYAK DAUN EUCALYPTUS UROPHYLLA DENGAN METODE SOXHLETASI - Irvan, Putra B. Manday, Januar Sasmitra (Universitas Sumatera Utara, 2015)
Eucalyptus urophylla plants (family: Myrtaceae, order: Myrtales ) usually are used only wooden parts for the manufacture of frames, pulp and paper, whereas their leaves can be used to produce essential oils in the pharmaceutical usage. The aim of this research is to extract the essential oils from leaves of Eucalyptus urophylla with soxhlet extraction method, in order to obtain maximum recovery of essential oils with good quality. Prior to the extraction process, the fresh leaves of Eucalyptus urophylla were reduced so that its size become 1 × 1 cm, and then dried in an oven at a temperature of 70 °C for 1 hour after being wrapped in a filter paper, after that followed by the extraction of the leaves using a variety of solvents, namely 96 % ethanol, n-hexane and dichloromethane, then proceed with the analysis of essential oil products (cineol content analysis). In this study, experiments were conducted with a variety of treatments such as the ratio of the volume of solvent to yield, the ratio of the mass of leaves of Eucalyptus urophylla to the yield on 5 cycles , and temperature of the solvent to yield. The conclusions of this research are the best extraction results with maximum cineol value (29.17 %) was obtained using dichloromethane solvent, while using 96 % ethanol produced the maximum yield of extract.